The Present Status of the Sociology of Health in Japan and its Future - YAMAZAKI, Yoshihiko (Japanese Sociological Review, 1998)
In this paper, four issues were discussed in regards to the status quo of the sociology of health in Japan from the viewpoint of its forthcoming development. First of all, it was stated why “the sociology of health” should be regarded as the abbreviation for “the sociology of health, illness and health/medical care, ” and its reasons were shown accordingly. Secondly, it was described that “the sociology of health, ” in the above mentioned interpretation, had diversified comprehensiveness and systems in both of its subjects and approaches; and that “the sociology of health” in Japan must be developed in overall aspects of its various fields and approaches. Thirdly, it was shown that the genesis and development of “the sociology of health” was closely related to the paradigm shift in the present health/medical care, meaning to be against a biomedical model and then for a social model, and that “the sociology of health” in Japan should be evolved in the proper correlation of such paradigm shift. Lastly, several issues in regards to the sociological studies of health were discussed, and the development of problem-oriented studies was thusemphasized.